2022
DOI: 10.1246/bcsj.20210372
|View full text |Cite
|
Sign up to set email alerts
|

Lactam Strategy Using Amide-Selective Nucleophilic Addition for Quick Access to Complex Amines: Unified Total Synthesis of Stemoamide-Type Alkaloids

Abstract: Our research group has been exploring a lactam strategy for the concise total synthesis of complex alkaloids. In this article, we report full details of the unified total synthesis of stemoamide-type alkaloids by chemoselective assembly of five-membered rings based on the lactam strategy. First, the concise and gram-scale synthesis of tricyclic stemoamide was achieved by vinylogous Michael addition-reduction sequence of an unsaturated γ-lactam with an unsaturated γ-lactone, followed by N-alkylation to form the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 128 publications
0
2
0
Order By: Relevance
“…In recent years, researches on the total syntheses and biological evaluation of Stemona alkaloids with different 5/7 bicyclic systems have garnered increasing interest, and more and more brilliant research works and review articles have been successively revealed. 4–13 Among the synthesized Stemona alkaloids, the pyrrolidone type alkaloids account for the most, followed by the pyrrole and pyrrolidine types. More importantly, the emergence of transformations among Stemona alkaloids with different ring systems has indeed improved the efficiency for rapid access to diverse alkaloids.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researches on the total syntheses and biological evaluation of Stemona alkaloids with different 5/7 bicyclic systems have garnered increasing interest, and more and more brilliant research works and review articles have been successively revealed. 4–13 Among the synthesized Stemona alkaloids, the pyrrolidone type alkaloids account for the most, followed by the pyrrole and pyrrolidine types. More importantly, the emergence of transformations among Stemona alkaloids with different ring systems has indeed improved the efficiency for rapid access to diverse alkaloids.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, the direct transformation of amides has been attracting increasing attention . Many methods have been developed for the selective reductive transformation of common amides 1 , that is, N- monoacylamines, into diverse classes of N -containing compounds (e.g., 2 and 3 ), which have been experiencing an evolution from using stoichiometric amounts of activating agents or reductants to catalytic reductive functionalizations (Figure , A). However, there are very few direct and general C–C bond forming reactions leading to non- N -containing compounds (Figure , B). This may due to the challenge for the chemoselective cleavage of C–N over C–O bonds of amides . Following the pioneering work of Ghosez and co-workers on the synthesis of cyclic ketones 4 from tert -amides and alkenes (Figure , B1), Hwu (Figure , B2), Charette (Figure , B3), Maulide, and our group ,, have developed few methods for the direct conversion of amides to alcohols 5 and ketones 6 .…”
mentioning
confidence: 99%